Evaluation of a digital programme for final year nursing students during COVID-19 - Jennifer Chipps; Martin Penelope; Hoffman Jeffrey; Williams Margaret; Baloyi Olivia; Walters Fiona; Mary Ann Jarvis (Elsevier, 2022)
Aim: The aim of this study was to evaluate a digital programme aimed to address COVID-19 related anxiety of final year undergraduate nursing students on returning to the clinical practice during the pandemic in South Africa. Background: In South Africa, concern about the physical and psychological safety of nursing students resulted in the planning of a psychological first aid program to facilitate nursing students return to clinical practice. Design: A survey was conducted in September 2020 following the August 2020 return of final year nursing students to clinical facilities. Methods: All final year nursing students were invited to participate in the study (N = 196). An online survey was circulated via WhatsApp asking respondents to rate their anxiety and fear of COVID-19 before and after return to practice following an intervention (eCOVID). Related pair analysis was done on the main outcome measures of anxiety, COVID-19 fears and concerns using Related Samples Wilcoxon Signed Rank tests. Results: After the programme, the respondents reported a significant reduction in anxiety (W = 2.92, p =.004) and COVID fear (W=0.3.1, p =.001), specifically related to infecting family, being exposed to COVID-19 at work, propagating infection at work and lacking access to COVID-19 information and communication. Conclusion: The implementation of a dedicated digital programme, underpinned by a sound theory base of psychological first aid, may have decreased anxiety and fear in nursing students during clinical practice in the pandemic.Contribution: The study contributes to evidence on psychological first aid support of nursing students during the COVID-19 pandemic.